Textbook analysis of integers content using the praxeology framework - Fitriasari, Putri; Suhendra; Suryadi, Didi; Nurlaelah, Elah (Jurnal Elemen, 2025)
Textbooks play a crucial role in the learning process, influencing instructional practices and students' cognitive development. However, some textbooks fail to support students in constructing new knowledge because of a lack of gradual concept progression. Consequently, textbook analysis has become a key focus of educational research. This study analysed a seventh-grade mathematics textbook on integers using the praxeology framework. It examines the material structure and identifies potential learning obstacles to learning. As part of Didactical Design Research (DDR) at the prospective stage, this study adopts an interpretive paradigm and qualitative approach. The praxeology framework, derived from the Anthropological Theory of the Didactic (ATD), serves as an analytical lens for this study. The researchers conducted an in-depth analysis of praxeological components, including task types, techniques, technologies, and the underlying theories. The findings revealed that the textbook systematically presented integer content but lacked support for epistemic knowledge construction. Additionally, potential didactic and ontogenic obstacles were identified. The findings contribute theoretically by demonstrating the framework’s application to textbook analysis. Practically, it guides the alignment of mathematical tasks with learning goals and reduces the learning obstacles. The results inform policy by emphasising the development of contextually and pedagogically relevant textbooks, rather than direct adaptation.